Perancangan E-Office Administrasi Pada Kantor Kelurahan Muara Bulian: Perancangan E-Office Administrasi Pada Kantor Kelurahan Muara Bulian - Agus; Ibnu Sani; Irawan; Agus Setiawan; Yulia (Jurnal PROCESSOR, 2021)
Management of administrative data at the Muara Bulian Village Office which is still conventional where data collection and reporting are still using bookkeeping, so that there is often difficulty in making letters, reports and searches, the absence of digital data back-up makes the administration process less efficient. So an efficient and effective information system is needed to support ticket sales bookkeeping. In addition, researchers also design computerized administrative applications. The benefit of this study is that it can improve the quality of service to the population. The results of this study are an administrative application as a tool for processing administrative data, letters and report generation. This application is expected to help employees of the Muara Bulian Village Office in providing the best service to the population. Keywords: E-Office, administration, Village Office